2009
DOI: 10.1177/0022034508327868
|View full text |Cite
|
Sign up to set email alerts
|

Biological Mechanisms in Palatogenesis and Cleft Palate

Abstract: Clefts of the palate are common birth defects requiring extensive treatment. They appear to be caused by multiple genetic and environmental factors during palatogenesis. This may result in local changes in growth factors, extracellular matrix (ECM), and cell adhesion molecules. Several clefting factors have been implicated by studies in mouse models, while some of these have also been confirmed by genetic screening in humans. Here, we discuss several knockout mouse models to examine the role of specific genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
163
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(176 citation statements)
references
References 156 publications
(133 reference statements)
3
163
0
10
Order By: Relevance
“…This process is mediated by transforming growth factor beta (TGFβ) signaling (reviewed in ref. 45). Our data support the concept that the CS Fgfr2 mutation does not affect the TGFβ-mediated fusion process.…”
Section: Discussionsupporting
confidence: 86%
“…This process is mediated by transforming growth factor beta (TGFβ) signaling (reviewed in ref. 45). Our data support the concept that the CS Fgfr2 mutation does not affect the TGFβ-mediated fusion process.…”
Section: Discussionsupporting
confidence: 86%
“…Lip development precedes palate formation, and therefore improper lip fusion may secondarily affect palate fusion. Thus, a cleft lip and palate often occur concurrently (Meng et al, 2009). Pax9 is essential for lip and secondary palate formation, and is required to regulate the normal shape of palatal shelves (Peters et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These processes are coordinated by secreted proteins and their signaling pathways, ExtraCellular Matrix components, and cell surface-receptors. 22 Gene targeting to knock-out specific genes in mice has generated, by the date, 84 lossof-function mutants that exhibits cleft palate. Information about these knockout models was collected from a literature review 4,21,23,50 and genes were clustered into families of cytokine/receptor, homeobox genes, and miscellaneous (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…21 The molecules involved in cleft palate formation in knockout models include cytokines, receptors, growth factors, ion channels, kinases, extracellular matrix proteins, homeobox genes, and transcription regulators 22,23 (Supplementary Table 1). According to the findings of this study, 46% of the cleft palate-causing genes (39 out of 84) were found to be affected by nicotine exposure.…”
Section: Several Genes Involved In Palate Development Are Affected Bymentioning
confidence: 99%